Revisiting Waqf Intention Prediction in Sumatera Utara - Khairunnisa, Khairunnisa; Ismail, Abdul Hadi; Shafitri, Olivia (Ihtifaz: Journal of Islamic Economics, Finance, and Banking, 2025)
Introduction to The Problem: Despite North Sumatra’s large Muslim population and economic capacity, its Waqf Index ranking remains among the lowest in Indonesia. This paradox raises questions about the underlying behavioral, institutional, and social factors that shape individual intention to participate in cash waqf. Purpose/Objective Study: This study aims to investigate the determinants of waqf behavioral intention by examining the influence of the Theory of Planned Behavior (TPB), Institutional Theory (IT), and Social Exchange Theory (SET). Design/Methodology/Approach:Using regression-based path analysis, this research analyzes responses from 100 individuals in North Sumatra collected via Google Form. Each construct (TPB, IT, SET) is operationalized through its subdimensions. Behavioral intention serves as the dependent variable. Findings: The results reveal that TPB significantly predicts waqf behavioral intention, while IT and SET do not show direct significance. TPB alone accounts for the most substantial influence, suggesting that attitudes, perceived social norms, and perceived behavioral control are key drivers of waqf participation in the region.